2021
DOI: 10.1039/d1ay01582f
|View full text |Cite
|
Sign up to set email alerts
|

High quantum yield nitrogen and boron co-doped carbon dots for sensing Ag+, biological imaging and fluorescent inks

Abstract: N, B-doped carbon dots with a quantum yield of 33.04% were developed as a sensor for Ag+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Using fluorescein dissolved in 0.1M NaOH solution (QY = 95%) as a reference, the QY of the G-CDs was obtained. 18 The calculation equation is as follows Eq. ( 1):…”
Section: Qy Measurementsmentioning
confidence: 99%
“…Using fluorescein dissolved in 0.1M NaOH solution (QY = 95%) as a reference, the QY of the G-CDs was obtained. 18 The calculation equation is as follows Eq. ( 1):…”
Section: Qy Measurementsmentioning
confidence: 99%
“…Protective shell materials, such as zinc sulde (ZnS) or zinc selenide (ZnSe), are oen used to enhance the quantum yield and stability of the QDs, ensuring consistent performance across different biological environments. 30 By carefully selecting and engineering the core and shell materials, researchers can create QDs with specic emission properties tailored to a wide range of imaging applications. This tunable emission capability, combined with their inherent brightness and stability, makes QDs an invaluable tool for advanced biological imaging and multiplexed diagnostics.…”
Section: Tunable Emissionmentioning
confidence: 99%
“…However, these assays also faced several challenges. For example, although most studies reported good to excellent LODs, their linear ranges were generally narrow, greatly limiting their practical applications [ 10 , 12 , 13 , 14 , 15 ]. Some studies reported relatively good LODs and linear intervals; however, their practicality for natural water sensing was not demonstrated [ 11 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported relatively good LODs and linear intervals; however, their practicality for natural water sensing was not demonstrated [ 11 , 16 , 17 , 18 ]. Furthermore, far fewer assays have demonstrated the detection of Ag + in biological samples (i.e., serums) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Lastly, the sensing mechanisms of most reported studies have not been fully discussed [ 12 , 14 , 16 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%